THE EFFECT OF PROFITABILITY ON THE RELATIONSHIP BETWEEN ASSETS STRUCTURE, BUSINESS RISKS AND CAPITAL STRUCTURE - Badri, Rico Elhando; Putri, Anandha Sartika (JURSIMA, 2022)
The purpose of this study was to find the effect of asset structure on capital structure, the effect of business risk on capital structure, profitability variable capable of moderating asset structure on capital structure, and profitability variable able to moderate business risk on capital structure. The type of the research was a quantitative research . The data collection technique in this study used purposive sampling, with a sample of 20 companies in the coal mining sub-sector listed on the IDX in 2016-2020. The data analysis method in this study used the panel data regression using Eviews 10. The result of this study found that asset structure had a positive and significant effect on capital structure, business risk had a negative and significant effect on capital structure, profitability was able to moderate asset structure on capital structure, but profitability was not able to moderate business risk to capital structure.